2021
DOI: 10.1007/s10639-021-10469-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing gamification e-quizzes based on an android app: the impact of asynchronous form

Abstract: Because of the heath measures taken during the outbreak of Covid-19, the lack of educational methods has become the primary concern among educational professionals who have been using technology as a motivational tool. Gamification is very important because it helps students to represent their study contents and enrich their experiences of higher education when learning in-person is unavailable during the Covid-19 period. This study seeks to present an Android-based gamification app to evaluate the effect of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…In accordance with Crisol-Moya et al [30], our results show a positive attitude toward active learning, plus these methodologies foster interdisciplinarity and, in the case of the role-play game, promote the development of learning tools, group work, and empathy. As other studies have previously shown, this teaching practice improves the development of communication skills and active listening as well as increasing the enthusiasm and motivation of students, as for other gamification methods [1,8,26,31]. However, this is the first study where a role-play game has been applied to teaching in veterinary medicine.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In accordance with Crisol-Moya et al [30], our results show a positive attitude toward active learning, plus these methodologies foster interdisciplinarity and, in the case of the role-play game, promote the development of learning tools, group work, and empathy. As other studies have previously shown, this teaching practice improves the development of communication skills and active listening as well as increasing the enthusiasm and motivation of students, as for other gamification methods [1,8,26,31]. However, this is the first study where a role-play game has been applied to teaching in veterinary medicine.…”
Section: Discussionmentioning
confidence: 81%
“…Today's world and the way that undergraduate students see the world have made teachers need to adapt to these changes, aiming for the goal that students become professionals capable of solving problems and that the innovative pedagogical practices can be useful tools for students to actively participate in the learning process [24]. The use of gamification and educational videos have been one of the methodological alternatives that have been used for this purpose [25,26]. Within the use of games as a tool for interactive learning, one of the most used methodologies has been role-play, mainly in areas where the communication skills and empathy are more relevant for professional development [8,9,27].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of universities used online proctoring systems, such as artificial intelligence‐driven proctoring systems (eg, Jia & He, 2021 ), when assessing student learning during lockdowns (Raman et al., 2021 ). Instead of focusing on online tools for summative assessment, however, researchers also explored the importance of “formative assessment” (eg, Sharadgah et al., 2020 ) and associated tools (eg, Areed et al., 2021 ) in supporting active online learning. Other technological innovations investigated in Cluster 1 range from “simulation”, “social media” and “telemedicine.” In particular, Facebook and Twitter emerged as the main social media used for “communication” during the quarantine (eg, Greenhow & Galvin, 2020 ; Zarzycka et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile two types of learning strategies were used in this study, gamified e-quizzes using a mobile application and paperbased quiz learning through traditional teaching (Areed et al, 2021), the results showed that student scores in the gamified equizzes were higher compared to those who participated in traditional paper-based quizzes. Accordingly, the finding also demonstrated that the students who participated in the gamified e-quizzes indicate more competency and students improved their ability to learn and master new skills both in and out of the classroom.…”
Section: A Gamified Online Assessment Environmentmentioning
confidence: 98%